Family Quality of Life in Foster and Adoptive Families of People with IDD - García-Sanjuán, Noemí; Berástegui, Ana; Mota, Rosalía (Scandinavian Journal of Disability Research, 2024)
The aim of this study is to examine the family quality of life (FQoL) in foster and adoptive families of people with intellectual and developmental disabilities (IDD). Adoption or foster care and IDD can have a specific impact on families, creating particular support needs. This study assesses self-reported parent FQoL and its relations with placement and disability factors in a convenience snowball sample of 62 foster and adoptive families of children, adolescents, and young adults with IDD in Spain. The FQoL ranged between moderate and entirely satisfactory (M = 92.2; SD = 16.9). Families of people with Down Syndrome (DS) and in special placements showed higher FQoL scores than those without other diagnoses or in ordinary placements. In contrast, increased mental health needs can explain a decrease in FQoL (β = –0.337, t = –2.729, p = 0.008). These families also show specific support needs essential for FQoL, including accurate information and training processes, and particular attention and support when a disability is identified after placement.
Keywords: adoption; foster care; intellectual and developmental disabilities; special needs children; quality of life; Scopus